Evaluation of Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) of UMKM on Salted Fish Processing in Pemangkat District - Nurhafisa, Eysi; Pebrianti, Nurzalina; Asarif; Jojo; Haliza (PAKIS JOURNAL INSTITUTE, 2024)
Sintete Hamlet, Pemangkat District, Sambas Regency, is a location located in a village that can be said that almost all residents in the village have a fish-based processing production business. One of the processing production businesses in this village is a salted fish processing business. The material in this salted fish processing uses shark, gutter fish and mackerel. However, the processing and packaging process still does not apply GMP and SSOP properly. This is due to the limited knowledge of the community regarding sanitation and GMP in the production process. This study aims to evaluate the application of Good Manufacturing Practices (GMP) and Santitation Standard Operating Procedure (SSOP) at the stages of the salted fish processing process in Pemangkat District, Sambas Regency, West Kalimantan. This research uses survey methods and direct interviews with sources to obtain primary data. The interviewee is an owner of salted fish UMKM. Based on the results of the research that has been done, it can be concluded that the processing of salted fish in Pemangkat District, Sambas Regency, West Kalimantan has not implemented Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedure (SSOP).